KEDUDUKAN DAN KEWENANGAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM ERA REFORMASI - Ah. Mujib Rohmat (UNISSULA, 2016)
Amendment 1945 to the beginning of the Reformation (1999-2002) led to a fundamental change in the position and authority of the Assembly. When the previous General Assembly is the highest state institutions with enormous power turned intostate institutions “normal” position in line with other state institutions such as the Parliament, the President, and the Supreme Court. When the previous General Assembly has the authority so large that after the changes, the authority is reduced, no longer authorized to elect the President and Vice President, the President and / or Vice President in his tenure as easy, and organize the lines of state policy (includingguidelines on therein).The decline position and a reduction in the authority of the Assembly is a positive impact on the state system and our democracy. With the position of the Assembly in line with the institutions of other countries then realized mutual control and balance (checks and balances) between branches of state power that can be prevented or minimized the abuse of authority, violation of the constitution, and the attitude / authoritarian andrepressive policies of a state institution. Reduced authority of the General Assembly so that it no longer has enormous power, even indefinitely have a positive impact, namely to prevent potential violations of constitutional or human rights as well as the development of democratic life quality.